Analisis Implementasi Model Outcome-Based Education (OBE) Pada Tiga Pilar Pembelajaran PAI DI Man Kuala Kapuas - AHMAD HUSIN; Hairunnisa (STAI Kuala Kapuas, 2026)
This study aims to analyze the implementation of the Outcome-Based Education (OBE) model across the three pillars of Islamic Religious Education (PAI) instruction at MAN Kuala Kapuas: planning, implementation, and evaluation. A qualitative approach with a case study design was employed, involving the madrasa principal, PAI teachers, and students as research subjects. Data collection involved observation, in-depth interviews, and document analysis, while data analysis utilized the interactive model proposed by Miles, Huberman, and Saldaña, comprising data condensation, data display, and conclusion drawing. The results indicate that the implementation of the OBE model in PAI instruction has proceeded quite well, particularly regarding planning, which is already aligned with outcome-based learning achievements. During the implementation phase, teachers have adopted strategies oriented toward student competency attainment, although variations in the specific methods applied remain evident. Regarding evaluation, assessment practices have shifted toward comprehensively measuring learning outcomes, yet they are not yet fully standardized in accordance with OBE principles. Supporting factors include institutional commitment, teacher competence, and the availability of learning facilities, whereas inhibiting factors include limited in-depth understanding of OBE and a lack of continuous training. The study implies that strengthening teacher capacity and aligning evaluation systems are essential to optimizing OBE implementation in PAI instruction.